Knowledge and Attitudes about organ donation in students of Health Sciences from a National University of Lambayeque - 2019: Conocimientos y Actitudes sobre donación de órganos en estudiantes de Ciencias de Salud en una Universidad Nacional de Lambayeque. 2019 - Cabrejos Montalvo, César A. (2021)
Objective: Determine the level of knowledge and attitudes about organ donation and xenotransplantation in students from a National University of Lambayeque. Methods: The sampling carried out was probabilistic of a simple random type and the sample was made up of 100 university students. An observational, descriptive and cross-sectional study was conducted to assess levels of knowledge and attitudes about organ donation. A survey of 20 dichotomous key questions was applied. Results: 53 women (53.0%) and 47 (47.0%) men were interviewed. It was observed that 76% do not know about the Law on the Promotion of Solidarity Donation of Human Organs and Tissues in Peru. Likewise, 96% know the organs and tissues that can be donated, 61% of the students have talked with their family about the subject of organ donation. 76% would be willing to donate their organs or tissues after life, and 88% would donate their relatives' organs to save the life of another relative. Conclusions: In the Faculty of Biological Sciences of the University it was observed that the knowledge of young people about organ donation was acceptable, although certain aspects need to be clarified.